Calculation of Tax Effective Yields for Discount Instruments - Colin, J. W.; Bayer, Richard J. (Journal of Financial and Quantitative Analysis, 1970)
This paper proposes a model that a dealer or investor may employ in determining• The potential investment value of a debt instrument, • The potential gains in net after-tax yield which result from swaps, and• The trade-off, effective, after-tax yield on a municipal vs a taxable corporate bond of the same quality or rating.